Nineteenth century black and white US statures: the primary sources of vitamin D and their relationship with height - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2008)
Vitamin D is vital in all vertebrates because it allows them to absorb more calcium from their diets, contributing to stronger skeletal systems and stature growth. Using a new source of 19th century US state prison records, this study contrasts the statures of comparable African-Americans and whites by the primary sources of vitamin D production: time exposed to solar radiation, skin pigmentation, and nativity. Greater insolation (vitamin D production) is documented here to be associated with taller black and white statures, and a considerable share of the stature differential by socioeconomic status was related to insolation.
Keywords: I10; J01; J15; J16; N81; 330; Socioeconomic status; vitamin D; insolation; 19th century US statures; Lebensstandard; Farbige Bevölkerung; Weiße; Klima; Soziale Ungleichheit; USA